IMPLEMENTASI SISTEM APLIKASI PEMESANAN MAKANAN MENGGUNAKAN METODE COLLABORATIVE FILTERING PADA FOOD COURT BERBASIS WEB - Maskhul Ryan Ibrahim; Rudi Susanto; Nurchim Nurchim (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Software has become very important for human life due to the rapid growth of the information and communications technology industry. Foodie is a web-based food ordering system used in food courts, one example of software engineering. By using the Collaborative Filtering (CF) method, this research aims to determine user food predictions. So far, the ordering system in the food court still requires customers to wait to order the menu they want, which reduces time effectiveness. This application was designed using the Waterfall Method for system development and JavaScript as the programming language. Some of the features produced by this application include login and registration menus, viewing menu lists provided by sellers in the food court, displaying menu prices, and order checkout process menus. With this web application, the author hopes to help users by offering a reliable food ordering application that will make it easier for them to choose items from the menu through a recommendation system.